The Position Of The Will In The Distribution Of Inheritance Reviewed From Islamic Law (Study of the Religious Court of Bengkulu Decision No. 0175/PDT.G/2012/PA.BN) - Mitaria Ningsih; Sirman Dahwal; Akhmad Muslih (Universitas Bengkulu, 2022)
This research raised the issue of the judge's consideration in the decision no. 0175/Pdt.G/2012/PA-Bn, regarding the position of the will in the distribution of inheritance. This study used a normative juridical law method, with primary legal material from the Religious Court of Bengkulu decision no. 0175/PDT.G/2012/PA.BN which has permanent legal force, and legal materials in the form of secondary laws, books, fiqh books that were related to the topics to be discussed. After the legal material was obtained, it was then analyzed based on normative descriptive analysis. The results of the study showed that (1) a will must be made by the heirs before the inheritance was divided. When the conditions and principles of the will have been fulfilled, the will became enforceable and has legal force after the death of the testator. Therefore, the position of will here in Islamic law did not necessarily constitute a kind of manipulation or violation of the law in relation to the application of Islamic inheritance law. (2) In case No. 0175/Pdt.G/2012/PA.Bn, that the dispute over the revocation of the will, the judge made a decision accordingly with Islamic Shari'ah law on wills. The will was designed and signed by the testator in the presence of two witnesses, and according to the judge's consideration, the will was valid based on the provisions of Article 195 (1) of the Criminal Procedure Code, then the judge's decision determined that the will was valid, so the judge must decide to impose sanctions on the Plaintiff and Defendant to divide the object of the case.